6(y 7)

Question

Asked 7/11/2012 1:01:42 AM

Updated 4/25/2014 12:09:38 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/25/2014 12:09:11 AM]

eturker|Points 2394|

nose|Points 871|

johnlennons|Points 794|

Expert answered|thewolf010|Points 1130|

Question

Asked 7/11/2012 1:01:42 AM

Updated 4/25/2014 12:09:38 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/25/2014 12:09:11 AM]

Rating

(x + 7)(x - 3) **Weegy:** 1/x+8=x-3/12
Multiply both sides by (x+8) gives 1 = (x+8)(x-3)/12
(x+8)(x-3) = 12
x^2 + 5x -36 = 0
Factorising gives
(x+9)(x-4)=0
x = -9 or 4 **User:** (x+1)(x^2+5x-2) **Weegy:** x^(3)+6x^(2)+3x-2 is the answer. (More)

Question

Expert Answered

Updated 6/13/2014 1:41:50 AM

2 Answers/Comments

(x + 7)(x - 3)

= x^2 - 3x + 7x - 21

= x^2 + 4x - 21

= x^2 - 3x + 7x - 21

= x^2 + 4x - 21

Added 6/13/2014 1:40:02 AM

This answer has been confirmed as correct and helpful.

(x+1)(x^2+5x-2)

= x^3 + 5x^2 + x^2 - 2x + 5x - 2

= x^3 + 6x^2 + 3x - 2

= x^3 + 5x^2 + x^2 - 2x + 5x - 2

= x^3 + 6x^2 + 3x - 2

Added 6/13/2014 1:41:50 AM

This answer has been confirmed as correct and helpful.

27,357,834

questions answered

There are no comments.